Maximal accumulated oxygen deficit in running and cycling - Hill, D. W.; Vingren, J. L. (Applied Physiology, Nutrition, and Metabolism, 2011)
The purpose of this study was to compare values of maximal accumulated oxygen deficit (MAOD; a measure of anaerobic capacity) in running and cycling. Twenty-seven women and 25 men performed exhaustive treadmill and cycle ergometer tests of ~3 min, ~5 min, and ~7 min duration. Oxygen demands were estimated assuming a linear relationship between demand and intensity and also using upwardly curvilinear relationships. When oxygen demand was estimated using speed (with exponent 1.05), values for MAOD for the three running tests were virtually identical; the mean of the three values was 78 ± 7 mL/kg. Use of an oxygen demand that was estimated using work rate (with exponent 1.00) generated the most similar values for MAOD from the three cycling tests (mean of 59 ± 6 mL·kg-1). Consistent with the higher (p < 0.05) MAOD in running, peak post-exercise blood lactate concentrations were also higher (p < 0.05) in running (13.9 ± 2.2 mmol/L) than in cycling (12.6 ± 2.4 mmol/L). The results suggest that the relationship between oxygen demand and running speed is upwardly curvilinear for the speeds used to measure MAOD; the relationship between demand and cycle ergometer work rate is linear; MAOD is greater in running than in cycling.